A study of posterior reversible encephalopathy syndrome in patients with eclampsia - Garag, Seeta; Janvekar, Mubashira (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The association of posterior reversible encephalopathy syndrome with eclampsia has recently received a lot of attention recently. Advances in Imaging has led to better understanding of the pathophysiology of eclampsia. Present study was undertaken to study the clinical characteristics of patients with eclampsia with PRES. Methods: This is a prospective observational study of 50 cases of Eclampsia with PRES in a period of 1 year. Patients admitted with Eclampsia were subjected to neuroimaging with CT or MRI and those with diagnosis of Posterior Reversible Encephalopathy Syndrome were included in the study and clinical profile analyzed. Results: Total of 50 patients were studied in the period of 1 year. The average age of patients was 21.8 years, majority of them residing in rural areas (74%) and 72% were referred cases. Conclusions: PRES is now identified as core component of Eclampsia. More studies are required to compare the outcome of Eclampsia associated with PRES and without PRES.